Classroom Management in Basic Yellow Book Learning at The Pesantren - Hartono Hartono (Madrosatuna: Journal of Islamic Elementary School, 2020)
Pesantren are traditional Islamic educational institutions which are never used up to be discussed and studied. One of the exciting things to study is how pesantren design basic "classes" so that they can make effective and efficient learning while staying oriented towards learning goals. And how do pesantren make "class" a secure emotional connection between teacher (kyai), student (santri), and teaching material (kitab kuning) in the class so that class harmonization appears within the typical scope of pesantren-style learning. Kitab Kuning learning in pesantren has a unique "model" in carrying out its education; this particularity is then interesting to be used as study material as another alternative in organizing education. Kitab Kuning learning in pesantren adheres to management that is different from class management in general, both in terms of curriculum structure, class construction, and interaction of existing learning components. In general, Kitab Kuning learning in pesantren is divided into 3 (three) levels, namely the primary level (Ula), the intermediate level (Wusta), and the upper level (Ulya). However, this research focuses more on the basic level (Ula), because this level is a determinant of success at the next grade level. Santri at the elementary level are not directly taught the Kitab Kuning, but were introduced first how to read and write the ‘Pegon’ Script. So, students who just entered were conditioned in such a way as to be more familiar with the ‘Pegon’ Script. Therefore, it will be discussed about the patterns and models of class management in the learning of the Kitab Kuning at As-Sunniyah Kencong Pesantren and Baitul Arqom Balung Pesantren in Jember Regency using behavior modification, socio-emotional, and group process approach, which is seen in the classroom conduciveness based on class conduciveness, the element of spirituality, namely the synergistic and harmonious interaction between the kiai, the teacher, and the santri in achieving the learning objectives.